O escudo de Aquiles e a tensão entre guerra e mousiké no canto XVIII da Ilíada - Werner, Christian (2022)
The purpose of this paper is to discuss how the tension between the destruction of war and the experience provided by musical activities or, mythopoetically, to the sphere of the Muses (mousiké), permeates Iliad 18, culminating in the narration of the forging of Achilles' new shield by Hephaestus. The main passages discussed are the meeting of the Nereids as a khóros that participates in Thetis' lament for Achilles the way Achilles conceptualizes his former set of weapons and some of the aspects highlighted in the actual meeting of Thetis and Hephaestus. As for the Shield, in addition to tracking the tension between destruction and mousiké that pervades it, it is shown how this tension helps to clarify two sets of problematic verses, 535-38 and 604-5.